The Role of Sharia Monetary Instrument in Liquidity Management and Performance Improvement of Islamic Banking Financial in Indonesia - Muwazir, Mohd Rizal; Anwar, Deky; Ab Ghani, Ab Mumin (al-'adalah, 2018)
This study analyzes the variables of liquidity and financial performance of Islamic banks that affect the number of transactions in Islamic monetary instruments. The aim is to find out which instruments is better in supporting liquidity management and financial performance of Islamic banks in Indonesia. This study uses the CAR and FDR variables as proxies of liquidity and ROA as a proxy for the financial performance of Islamic banks. While the proxy for sharia monetary instruments in Indonesia is the variable SBIS and SBPUS. This study uses monthly Islamic banking reports in Indonesia for the period January 2015 to September 2017. Data is processed and analyzed by Augmented Dickey-Fuller (ADF) Stationery Test as a way of testing stationary data and then testing hypotheses using Vector Autoregression (VAR). This study found that the the most contributing variable to the changes in transaction volume in Islamic monetary instruments was the variable liquidity, namely CAR and FDR. In Addition, SBIS sharia monetary instruments are better used by Islamic banking in Indonesia compared to SBPUS.